ANALYSIS OF FARMERS COMPETENCIES IN PANGGUNGREJO UTARA - Noviasari, Ledy Diana Gilam; Handayati, Yuanita (Journal of Business and Management, 2017)
Abstract. Background - Competency is ability, knowledge, and skill of people in some condition. In the agricultural sector, competency can classify in technical skill, managerial skill, and entrepreneurial skill of farmers. The technical skill there are planting, fertilization, irrigation, control pest and diseases, harvesting and also post-harvesting. Other than technical skill, managerial skill also can categorize in planning, networking, and managing finances. Sales strategy also used for main concern in the gap of the crop. On entrepreneurial, there are taking a risk for farmers, opportunity in the cocoa field, creativity and also problem introspection. Objective - The study aim to analyze the competency of farmers and clustering farmers based on their skill. Method - The clustering of competency has objective to improve farmerâ€™s skill and increasing the cocoa crop. So, because of that, cluster analysis is used to the research methodology. Result - The result of the method is farmers have 3 clusters. Each of cluster has different of characters. Cluster 1 is farmers with technical skill, managerial skill and entrepreneurial skill lower than other farmers in cluster 2 and 3. Cluster 2 are farmers that have high managerial skill than cluster 1 and cluster 3. And for cluster 3 are farmers with high competency in entrepreneur skill and technical skill but for the managerial skill is medium skill, almost same with cluster 1.. Conclusion - To increase crop in their farming, farmers must improve their competency. The solution that can do with the discussion and telling experience in farming. So, with this data, farmers could sharing, helping one and others to improve the farming competency of farmers without waiting for training from the government program or private organization that has the aim to help them.Â Keywords: competency, cocoa, technical, managerial, entrepreneurial, farmer, cluster.